PENCIPTAAN BUKU ILUSTRASI LEGENDA TARI JARAN KENCAK SEBAGAI UPAYA MEMPERKENALKAN BUDAYA LUMAJANG KEPADA ANAK-ANAK - Challtis, Phebii Kurnia Diajeng; Fianto, Achmad Yanu Alif; Hidayat, wahyu (Jurnal Art Nouveau, 2015)
Abstract: The purpose of research is creating ilustration book by Jaran Kencak it presents Lumajang culture for the children. Nowadays, local culture has been forgotten from the young generations who were affected by foreign culture. It was caused foreign culture more modern. It made the young people not knowing their own tradition. Where as tradition dance must be keep, develop and know it. We can get values and benefits for intelligence, social and personality.Keyword : Ilustration Book, Design, Local Culture, Traditional Dance, Children